Questioning Across Contexts: A Comparative Analysis of Higher-Order and Lower-Order Questions in CLIL and EMI - Hughes, Bronwen; Rasulo, Margaret (ALLiED, 2025)
This study investigates questioning techniques in Content and Language Integrated Learning (CLIL) and English Medium Instruction (EMI) classrooms, focusing on higher-order and lower-order questions as key pedagogical tools for language acquisition and content comprehension. Drawing on Bloom’s Taxonomy, the research categorizes lower-order questions as those fostering recall and comprehension, while higher-order questions promote critical thinking, analysis, and synthesis. Conducted in Italian high schools and universities, the study utilized classroom recordings of CLIL and EMI lessons in science and economics to examine the use of questioning techniques by teachers and the elicited responses from students. The findings reveal that lower-order questions provide essential scaffolding for language and foundational content, which is crucial in multilingual classrooms where students are often learning through a non-native language. The study underscores the effectiveness of combining both question types to balance comprehension with deeper cognitive engagement. In CLIL and EMI contexts, the sequential use of lower-order questions for foundational understanding and higher-order questions for analytical depth promotes a holistic approach to learning. By implementing a qualitative approach to the analysis of dialogical questioning, this study provides evidence that an integrated questioning strategy fosters a dynamic, inclusive learning environment, enabling students to progress from basic knowledge acquisition to critical, independent thinking skills.